Physicochemical Characteristics of undrainable Water Dams Utilized for Fish rearing In The Semi-Arid Naromoru Area, Central Kenya - Mwangi, Benson M.; Kairu, E.; Ndiwa, C.T.; Kaluli, J.W.; Nyingi, D. (Jomo Kenyatta University of Agriculture and Technology, 2012)
Naromoru is a semiarid area in Central Kenya, occurring on the leeward side of Mt. Kenya. Its water sources include a few permanent rivers such as Nairobi River, intermittent streams and a large number of undrainable water reservoirs. Most of the undrainable water resources have been stocked with fish but their utilization for fish rearing has generally remained very low. The purpose of this study was therefore to examine the water quality status of the dams to assess their suitability and potential for fish production. pH, electro-conductivity and total dissoved solutes (TDS) were measured in-situ from three reservoirs (Gathathini, Lusoi and Kianda dams) differing in their habitat characteristics. Water samples were collected for determination of the ionic concentartions of the reservoirs. Water quality status differed markedly between sites, with electric conductivity ranging from 350μScm-1 at Gathathini dam to over 1350μScm-1 at Lusoi dam. pH however showed only a slight variation from 8-9.6. Water temperature and transparency varied significantly between the sites, while cationic constituents (Ca2+, K+, Mg2+ and Na+), anions (SO4 2-, HCO3 2-, and Cl-1), heavy metals (Pb2- and Cu2+) and nutrients (NO3 - and PO4 2-) were all within the recommended WHO levels for fish production. Generally the water quality status was within the standards recommended for fisheries production
Keywords: Mt. Kenya; limnology; fisheries; productivity